Theoretical Study of the [4+2] Cycloaddition Reaction of Trifluoroethylene with Five-membered Chalcogens Heterocyclic Compounds - Mohammad-Salim, Haydar A.; Abdallah, Hassan H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
[4+2] cycloaddition reaction has enormous significant in organic chemistry synthesis reactions and yet remains unexplored for the synthesis of fluorine-containing compounds. A density functional theory study of the stereo- and regioselectivity of the [4+2] cycloaddition reaction of trifluoroethylene with furan, thiophene, and selenophene was carried out in the gas phase. The B3LYP functional is used throughout in combination with 6-31G(d) basis set. The analysis of stationary points and the energetic parameters indicates that the reaction mechanism is concerted and confirms that the exo-adducts are thermodynamically and kinetically more favored than endo-adducts. The calculated branching ratio indicates that the exo-adducts have the higher percent yield than endoadducts and the yield of endo-adducts is increased only slightly on proceeding from furan, through thiophene, and onto selenophene. The analysis of the frontier molecular highest occupied molecular orbital (MO) and lowest unoccupied MO orbitals indicates that the exo-adducts are more stable due to their higher energy gab. The reaction energies were compared to the MP2/6-31G(d) and CCSD(T)/6-31G(d) calculations.